Tastemakers and tastemaking : Mexico and curated screen violence - Thornton, Niamh (Albany : State University of New York, 2020)
"Considers how and why taste persists in the analysis of Mexican film and television by looking at key figures and their impact on the curation of violence"--
Questions of taste: classification, value, legitimation, and Distinction -- Cultural institutions and taste formation: Nelson Carro and the Cineteca in 2010 -- Commonplace and routine: Amat Escalante's extreme realism in Los bastardos (2008) and Heli (2013) -- Re-versioning and thick contexts: the cinematic adaptations of Los de abajo -- Bodily excess and containment: Bordertown (Gregory Nava, 2006) and The Virgin of Juarez (Kevin James Dobson, 2006) -- Curating cruelty and criminality: the radical mediation of Kate del Castillo -- Conclusion.
Includes bibliographical references, filmography, and index.
Description based on online resource; title from PDF title page (ProQuest Ebook Central, viewed on December 09, 2020).
JSTOR
Keywords: Motion pictures -- Mexico -- History and criticism; Motion pictures -- Aesthetics; Television -- Aesthetics; Curatorship -- Philosophy; Television programs -- Mexico -- History; Violence in motion pictures; Violence on television; Cinéma -- Mexique -- Histoire et critique; Cinéma -- Esthétique.; Télévision -- Esthétique.; Conservation -- Philosophie; Émissions télévisées -- Mexique -- Histoire; Violence au cinéma.; Violence à la télévision.; History & Criticism; Mexico; Latin America; HISTORY; Television; PERFORMING ARTS; Aesthetics; PHILOSOPHY; Popular Culture; SOCIAL SCIENCE; Media Studies; Film & Video; Motion pictures; Motion pictures -- Aesthetics; Television -- Aesthetics; Television programs; Violence in motion pictures; Violence on television; Mexico; Electronic books; Criticism, interpretation, etc; History